Interest rate and income disparity: Evidence from Indonesia. (15th November 2020) - Husain, Shaiara; Sohag, Kazi; Hasan, Rajibul; Shams, S. M. Riad
Abstract: We highlight the most adverse impact of capitalism on inequality through the channel of the interest rate. The interest rate has been an instrument of capitalism which aggravates the accumulation of wealth in the hands of very few people and thereby worsens inequality. To this end, this article scrutinises the dynamic impact of financial development on income inequality in the context of Indonesia, applying DOLS and FMOLS approach by analysing time series data over the years of 1984 to 2018. Rising income inequalities has been a common perpetuating trend of East Asian countries among which we find the case of Indonesia worth interesting to study while filling up the gap in the existing literature. We provide evidence that interest rate exacerbates income inequality in the long‐run economy of Indonesia. Financial development in the early phases of development favours economic activity in the urban sector based on capital intensive technology which does not help absorb excess rural labour. The empirical finding of this study profoundly demonstrates one of the substantial drawbacks of capitalism in terms of income disparity.